Superconducting and Electrotransport Properties of Y0.89R0. 11Ba2Cu3O7−δ (R=La, Pr) Polycrystals - Nikoghosyan, S. K.; Sargsyan, A. G.; Zargaryan, Y. G.; Aivazyan, A.; Hakopyan, A.
The superconducting and electrotransport properties were studied in Y0.89R0.11Ba2Cu3O7−δ polycrystals, with the same concentration of rare earth metal elements (R = La, Pr) but with different valence and magnetic moments, by recording the temperature dependence ρ(T) curves of the resistivity in the temperature range (77-300) K. It was considered the influence of La and Pr on the width of the superconducting transition of the samples (ΤC), its critical temperature (determined by the onset of transition - ΤCon and the offset - Tc0), the absolute values of the resistivity of the fluctuation and normal regions ρ(300 K) and ρ(100 K)], as well as on their ratio [a = ρ(300 K)/ρ(100 K)]. It has been revealed that there is a certain correlation between the aforementioned characteristics. It is emphasized that Pr is more critical than La in terms of its effect on characteristics. It is believed that the different behavior of the correlations observed between these characteristics for La and Pr is largely due to the differences in their ionic radii, displayed valence, as well as their intrinsic magnetic moments. It is shown that these differences in the case of La and Pr are manifested in the form of the phase separation phenomenon and the "Pr- anomaly", respectively.
Keywords: Physics